The Impact of International Management Strategies on the Quality of Implementation in Vertical Housing Projects a Case Study in the Diyala Housing Department - Zeyad Baker Khuhdur; Husam Salah Sameen (Global Academy of Business Studies, 2026)
Purpose: This study explores how international management strategies can improve the execution quality in vertical housing projects. Research Methodology: A descriptive-analytical approach was used, based on insights from 42 professionals (project managers, engineers, and site supervisors) with direct experience in vertical housing projects. The study investigates the correlation between internationally-oriented management practices and the quality of execution on the ground. Results: The findings show a statistically significant positive correlation between the adoption of international management strategies and improved project execution. Projects using structured planning systems, accepted quality control standards, and managerial techniques were more compliant with technical requirements, more efficient in their work, and had better overall performance. Conclusions: The results underscore the strategic importance of international management strategies as a source of excellence in modern urban development projects. Integrating global best practices enhances coordination among project stakeholders and supports sustainable performance improvement in complex construction environments. The study emphasizes the need to institutionalize internationally-aligned management frameworks to ensure long-term quality and competitiveness in vertical housing projects. Limitations: The study relies on expert opinions, which may be subjective and context-dependent. Further empirical testing is needed with a larger sample across various regions and project types. Contributions: The research contributes empirical evidence on the relationship between international management strategies and project execution quality in vertical housing, offering a basis for developing globally-aligned management frameworks in the construction industry.